What is the influence of vocabulary size and the use of writing techniques in the proficiency of students in the level of academic writing that students reach in the English Composition II course, semester I 2015 at the Foreign Language Department of the Arts and Sciences School of the University of El Salvador - Cáceres Salinas, María José
The main purpose of this research project is to determine how vocabulary size and the use of writing techniques affect the process when students don’t the writing techniques and don’t apply enough vocabulary. The focus of our research will be on students of English composition II courses at the Foreign Language Department of the School of Arts and Science at the University of El Salvador. Since these students have already taken the Intensive English and Composition I and they are supposed to have reached a high level of proficiency English. Students from these course might use the results of this research to strength their English Proficiency that they have at the moment. Moreover through this research it will be determined the level of vocabulary these students have and also if they use writing techniques. Besides that the research aims at finding out which of these two important variables vocabulary size or the use of writing techniques is the one that influences the most in the student’s proficiency.